Screen-printed electrodes for electroanalytical sensing, of chromium VI in strong acid media - Miscoria, Silvia Alejandra (2014)
Simple, low-cost and acid-resistant carbon-based screen-printed electrodes (SPEs) addressed to detection of hexavalent chromium species, Cr(VI), in sulfuric acid at pH about 1, were prepared and characterized. Working and counter electrodes were prepared jointly on the same substrate in a single strip (working-counter electrodes pair). The batch printing process allowed obtaining many working-counter electrode pairs in a unique step. The developed working electrodes are comprised of several layers deposited on an alumina substrate: (1) bottom silver conductor, (2) dense organic–graphite composite conductor, (3) active layer consisting of a porous organic–graphite composite which contains a Cr(III) ionophore for testing Cr(III) obtained after reducing Cr(VI), and (4) an insulating and protective dielectric. All materials except the bottom Ag conductor were made on an organic matrix based on a thermoplastic polymer, polyvinylbutyral (PVB). The amperometric determination of Cr(VI) species at pH 1 was performed over a wide concentration range (dynamic range 3 μM–40 mM). The range for linear amperometric response is 3 μM–10 mM, with sensitivity about 0.08 mA mM−1. The sensitivity is improved in comparison with previously developed sensors, while keeping a low limit of detection (LOD about 1 μM). The response of the sensors are not interfered by the presence of Cr(III) in the solution, although the sensor can detect local formation of Cr(III) at the electrode surface after the reduction of Cr(VI) when diethylenetriamine-pentaacetic acid (DTPA), a complexing agent for Cr(III) is incorporated into the pastes.